ANALISIS HUKUM ATAS INDEPENDENSI ARBITER - Dewi Rahma; Ariawan Gunadi (Fakultas Hukum Universitas Tarumanagara, 2022)
One of the problems that may arise when carrying out the process of resolving cases in arbitration is regarding theneutrality or independence of the arbitrators chosen by the applicant and the respondent to the arbitration. Althoughit is very rare, but in fact in some cases it can happen. The chosen arbitrator is indicated to be siding with one of theparties due to having blood relations with the Petitioner or Respondent, or may also have financial or other interestsin the arbitration award. If it is proven that an arbitrator is not independent in the arbitration dispute resolutionprocess, then the applicant or respondent may file a denial of the arbitrator. In practice, the reasons for impartialityand reasons for independence are the two main reasons put forward by the parties. This independence is defined asthe arbitrator's dependence on the party who appointed him and this dependence is not related to any relationshipor financial interest in the dispute. This independence intersects with the psychology of an arbitrator. For example,this can be seen in international disputes, where the arbitrator comes from the same nationality as one of theparties. Meanwhile, impartiality is more closely related to an arbitrator who is openly seen as siding with one party.For example, in a trade dispute where one of the parties is a trade organization and the chosen arbitrator is amember of that trade organization. This of course makes the arbitrator not neutral or partial.